Evaluation of repair bond strength with different methods for zirconia restorations - Galal, Rami M. (2023)
Analysis was done using graph pad Instat (graph pad, Inc.) software. Value of p ≤ 0.05 is considered significant. Homogeneity of variance and errors normal distribution confirmation was done; a 2-way analysis of variance (ANOVA) was performed.